Effects of Sn doping on the manufacturing, performance and carbon deposition of Ni/ScSZ cells in solid oxide fuel cells. (16th October 2020) - Arifin, Nor Anisa; Troskialina, Lina; Shamsuddin, Abd Halim; Steinberger-Wilckens, Robert
Abstract: This work demonstrates the effect of tin (Sn) doping on the manufacturing, electrochemical performance, and carbon deposition in dry biogas-fuelled solid oxide fuel cells (SOFCs). Sn doping via blending in technique alters the rheology of tape casting slurry and increases the Ni/ScSZ anode porosity. In contrast to the undoped Ni/ScSZ cells, where open-circuit voltage (OCV) drops in biogas, Sn–Ni/ScSZ SOFC OCV increases by 3%. The maximum power densities in biogas are 0.116, 0.211, 0.263, and 0.314 W/cm 2 for undoped Ni/ScSZ, undoped Ni/ScSZ with 3 wt% pore former, Sn–Ni/ScSZ and Sn–NiScSZ with 1 wt% pore former, respectively. Sn–Ni/ScSZ reduces the effect of the drop in the maximum power densities by 26%–36% with the fuel switch. A 1.28–2.24-fold higher amount of carbon is detected on the Sn–Ni/ScSZ samples despite the better electrochemical performance, which may reflect an enhanced methane decomposition reaction. Highlights: Effect of Sn addition with blend in doping method to tape slurry, green tape, and cell's porosity in SOFC fabrication via tape casting route. OCV increased by 3% in the Sn-NiScSZ cells while decreased by 7–12% in the undoped cells. 1.28–2.24-fold higher amount of carbon detected on Sn-NiScSZ cells despite of 26–36% better electrochemical performance.